Analisa Space Syntax pada Rumah Susun Lokbin Rawa Buaya Jakarta Barat - Sunoto, Asri Ardiati (Arsir, 2023)
Rawa Buaya Lokbin flats are buildings with commercial and residential functions. Two activities which different nature. That is why it is interesting to observe the infringements there. According to Hillier and Hanson, the basic concept of space syntax analysis consists of 3 types, namely Connectivity, Integration, and Intelligibility. Spaces with high connectivity level are the most potential for infringements compared with other with lower connectivity levels. This research aims to compare the connectivity level mapping (by space syntax method) with the compiling of the infringements mapping (through observation, literature study and in-depth interviews) on each floor. Based on the comparison, there is a discrepancy between predictions from Space syntax and empirical conditions. The red area (which is predicted to be the most frequent place of infringements) has little or hardly even infringements and conversely the blue area (which is predicted to be safe) actually has several infringements. There are several causes for this to happen, namely the intervention from the flat management to anticipate these conditions, lack of knowledge of the rule violators of some regulations, lack of facilities and the awareness of building users to comply with regulations is low.